EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, COMPANY SIZE, AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE IN GOODS CONSUMER COMPANIES IN INDONESIA STOCK EXCHANGE (IDX) - Melisa, Melisa (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to examine and analyse the effect of the current ratio, debt to equity ratio, firm size, and corporate social responsibility on firm values ​​both simultaneously and partially and to find out and analyse whether institutional ownership variables as moderating variables can strengthen or weaken the relationship between current ratio, debt to equity ratio, and company size to firm value in consumer goods companies on the Indonesia Stock Exchange. The population in this study were 39 consumer goods companies listed on the Indonesia Stock Exchange in 2015-2017. The sample was selected using 36 stratified random sampling methods, so that the study sample was collected as many as 108 observations. Testing the research hypothesis using multiple linear regression analysis and testing the moderating variable using the absolute difference test. The results showed that simultaneously the current ratio, debt to equity ratio, firm size, and corporate social responsibility had a significant effect on firm value. Partially the size of the company has a significant effect on firm value while the current ratio, debt to equity ratio, and corporate social responsibility have no significant effect on firm value. The moderating variable of institutional ownership is not able to moderate the current ratio relationship, debt to equity ratio, company size, and corporate social responsibility to firm value.